Precursors to aggression are evident by 6 months of age. Issue 3 (25th February 2014) - Hay, Dale F.; Waters, Cerith S.; Perra, Oliver; Swift, Naomi; Kairis, Victoria; Phillips, Rebecca; Jones, Roland; Goodyer, Ian; Harold, Gordon; Thapar, Anita; van, Stephanie
Abstract We tested the hypothesis that developmental precursors to aggression are apparent in infancy. Up to three informants rated 301 firstborn infants for early signs of anger, hitting and biting; 279 (93%) were assessed again as toddlers. Informants' ratings were validated by direct observation at both ages. The precursor behaviours were significantly associated with known risk factors for high levels of aggressiveness. Individual differences were stable from early infancy to the third year and predicted broader conduct problems. These findings suggest that some individuals set forth on the trajectory to high levels of aggression by 6 months of age. The findings have implications for developmental studies of aggression, clinical prevention and intervention strategies, and theoretical considerations regarding the detection of precursors in different domains of development.